Ecological compensation of agricultural heritage conservation: case of the mountainous Juglans hopeiensis planting system in Beijing - Du, Haixia; Xu, Guangcai; Lin, Yusen (Frontiers in Sustainable Food Systems, 2024)
Agricultural heritage, consisting of farmers' livelihood activities, experiential knowledge systems, and rural landscapes, is an integrated regional system with significant historical, cultural, and biodiversity value based on the natural environment and land use. Agricultural heritage is rich in traditional wisdom on the use of natural resources and is of great value in achieving the goals of sustainable agriculture and food security. The protection of agricultural heritage provides a favorable environment for farmers to engage in agricultural production, and provides a wide variety of potential agricultural production processes, thus adopting possibilities for the transformation of sustainable food systems. Ecological compensation can be an effective method for narrowing the development gap caused by heritage conservation. It can improve farmers' livelihoods in heritage sites and stimulate the enthusiasm of farmers to protect the agricultural heritage. Taking the mountainous Juglans hopeiensis planting system in Beijing as a case study, we evaluate the amount of ecological compensation using the contingent valuation method based on statistical data and interviews with farmers by combining with their willingness to accept compensation and income gap with other farmers. In addition, we analyze the factors affecting farmers' willingness to accept compensation. The results show that ecological compensation at a standard of RMB 9823.13 yuan/(hm² • a) can meet the livelihood needs of farmers in heritage sites, thus bridging the income gap between farmers in and around the heritage sites. Whether farmers accept compensation is mainly influenced by five variables: gender, education level, per capita income, household members, and the proportion of therapy walnut income in household income. We suggest that a concrete ecological compensation mechanism should be further constructed to ensure the effective implementation of ecological compensation and the longtime existence and development of agricultural heritage. This study can not only provide a reference for calculation of the ecological compensation amount and the establishment of ecological compensation mechanism for agricultural heritage in Beijing, but it is also crucial for the development of policies to ensure long-lasting conservation of agricultural heritage and continuous enhancement of farmers' livelihoods, and to improve the adaptation of global agricultural systems.